European training requirements for the specialty of medical genetics - Moog, Ute; Berg, Jonathan; Kerr, Siobhan; Turnpenny, Peter D.; Verloes, Alain; Zschocke, Johannes (European journal of human genetics, 2025)
The development of European training standards is a major contribution to the improvement of medical training at the European level and one of the core activities of the European Union of Medical Specialists (Union Européenne des Médecins Spécialistes, UEMS). European Training Requirements for the specialty of Medical Genetics (ETR-MG) were first developed and approved in 2017. Here we report the content and objectives of the 2023 revision, carried out by the ETR-MG Working Group and the officers of the UEMS Section of Medical Genetics in close cooperation with the ESHG and the European Board of Medical Genetics (EBMG). New aspects concern an update of the description of the specialty, the integration of the examination for the European Certificate in Medical Genetics and Genomics (ECMGG), a complete restructuring of the syllabus, and the adaption to novel concepts of medical education.
Gesehen am 03.11.2025